2021
DOI: 10.20527/infotek.v22i2.12387
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Orientasi Serat Dan Waktu Alkalisasi Pada Laminates Composite Polyester-Serat Bemban (Donax Canniformis) Terhadap Kekuatan Bending, Impact Dan Bentuk Patahan

Abstract: Plant Bemban (Donax canniformis) is one of the plants that is often found in the swamp area of South Kalimantan that grows wildly on the roadside and around the home garden. The purpose of this study is to find out how large the bending strength and composite impact is reinforced with bemban fiber with polyester matrix with variations in fiber orientation and alkalization time. The method is done by alkalizing the banana fiber with 4% NaOH solution with a variation of 30 minutes, 60 minutes and 90 minutes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
5
1
2
Order By: Relevance
“…Figure 12 composite fault cross-section with a volume fraction of 10%: 90% is that the composite has the highest strength value with a bending strength value of 105.5 Mpa. At the volume fraction of 10%: 90% is still visible at some point, there is a pull-out failure shown in figure 4.6; in addition to the pull-out found in the composite that reduces the bending force, it turns out that after the implementation of different magnification, debonding is seen in the composite [19]. Debonding is the release of binding force between the fiber and the matrix.…”
Section: Figure 11 Macro Photo Of Fault Form Tensile Testing Specimenmentioning
confidence: 98%
“…Figure 12 composite fault cross-section with a volume fraction of 10%: 90% is that the composite has the highest strength value with a bending strength value of 105.5 Mpa. At the volume fraction of 10%: 90% is still visible at some point, there is a pull-out failure shown in figure 4.6; in addition to the pull-out found in the composite that reduces the bending force, it turns out that after the implementation of different magnification, debonding is seen in the composite [19]. Debonding is the release of binding force between the fiber and the matrix.…”
Section: Figure 11 Macro Photo Of Fault Form Tensile Testing Specimenmentioning
confidence: 98%
“…Tumbuhan bemban dengan nama ilmiah Donax canniformis merupakan tumbuhan rumpun yang membentuk semak setinggi 1,5 -5 m. Bemban banyak ditemukan pada tepi-tepi air, tempat basah, atau juga hutan bambu dengan tumbuh secara liar [7]. Saat ini, bemban dimanfaatkan masyarakat sebagai bahan kerajinan tangan berupa anyaman dan tali [8].…”
Section: Pendahuluanunclassified
“…Bemban telah banyak dimanfaatkan dalam bidang komposit. Komposit serat bemban memiliki ketahanan paling baik dibandingkan serat lain yaitu 0,0449 Joule/mm 2 terhadap uji impak [9], nilai impak dan bending yang cukup tinggi yakni 0,0208 Joule/mm 2 dan 114,16 Mpa [10]. Pemanfaatan komposit sebagai chopped fiber composite mendapatkan nilai energi serap 0,0653 J/mm 2 [11].…”
Section: Pendahuluanunclassified
“…Bemban (Donax Canniformis) is a plant that grows naturally in swamp regions with acidic peat soil structure [2,3]. These regions are commonly found on the borders of bodies of water, in damp areas, bamboo woodlands, and even in the yards of houses, producing little islands [4]. Bemban is currently employed by the community to manufacture woven and roped handcraft products.…”
Section: Introductionmentioning
confidence: 99%
“…The alkalization process can lower the lignin and hemicellulose content in the fiber, improving the bond between the fiber and the binder [4,11] Furthermore, alkalization attempts to break down cellulose crystals, enhance porosity, and reduce fiber size, all of which will promote contact between surfaces thereby improving mechanical characteristics [12]. Saputra et al [13] found that International Journal of GEOMATE, Dec., 2023 Vol.25, Issue 112, pp.…”
Section: Introductionmentioning
confidence: 99%